Composite Fuzzy Logic Control Approach to a Flexible Joint Manipulator. (21st January 2013) - Ahmad, Mohd Ashraf; Tumari, Mohd Zaidi Mohd; Nasir, Ahmad Nor Kasruddin
The raised complicatedness of the dynamics of a robot manipulator considering joint elasticity makes conventional model-based control strategies complex and hard to synthesize. This paper presents investigations into the development of hybrid intelligent control schemes for the trajectory tracking and vibration control of a flexible joint manipulator. To study the effectiveness of the controllers, a collocated proportional-derivative (PD)-type Fuzzy Logic Controller (FLC) is first developed for the tip angular position control of a flexible joint manipulator. This is then extended to incorporate a non-collocated Fuzzy Logic Controller, a non-collocated proportional-integral-derivative (PID) and an input-shaping scheme for the vibration reduction of the flexible joint system. The positive zero-vibration-derivative-derivative (ZVDD) shaper is designed based on the properties of the system. The implementation results of the response of the flexible joint manipulator with the controllers are presented in time and frequency domains. The performances of the hybrid control schemes are examined in terms of input tracking capability, level of vibration reduction and time response specifications. Finally, a comparative assessment of the control techniques is presented and discussed.